Whether in comparison with the earlier inventories the cizye registers in XVIII century are doing the research of the demographic tendencies on the Balkans easier - Nenad Moačanin (Array, 2011)
The topic could be perhaps styled “the reliability of the Ottoman registers, etc.”. This is always the most important question. Since most of the Ottoman registers deal with the taxation, the next step in formulation might focus on the “reliability for estimations of agricultural production and demographic trends”.